A remark on wave breaking for the Dullin–Gottwald–Holm equation. Issue 11 (18th August 2017) - He, Fangyi; Wei, Zhiqiang
Abstract : In this paper, a new sufficient condition to guarantee wave breaking for the Dullin–Gottwald–Holm equation is established, which is a local criterion and easy to check.